Notas de una romería al Santuario de Nuestra Señora de Sonsoles (mayo de 1935) / An account of a pilgrimage to Sonsoles (May 1935) - Alfredo Méndiz (Studia et Documenta)
Transcription and commentary of an account written by St. Josemaría and Ricardo Fernández Vallespín of a pilgrimage they made to the Marian Shrine of Sonsoles in Ávila on May 2nd 1935. The custom of the May pilgrimage was born on that day.